Benzyl isothiocyanate promotes apoptosis of oral cancer cells via an acute redox stress-mediated DNA damage response. (November 2016) - Yeh, Yao-Tsung; Hsu, Yen-Nien; Huang, Sheng-Yun; Lin, Jian-Sheng; Chen, Zi-Feng; Chow, Nan-Haw; Su, Shu-Hui; Shyu, Huey-Wen; Lin, Ching-Chiang; Huang, Wu-Tein; Yeh, Hua; chih, Yu-chia; et al.
Abstract: Benzyl isothiocyanate (BITC) is a cruciferous vegetable-derived compound with anticancer properties in human cancer cells. However, its anticancer potential and underlying mechanisms remain absent in human oral cancer cells. Results indicate that BITC inhibits growth, promotes G2 /M phase arrest and triggers apoptosis of OC2 cells with a minimal toxicity to normal cells. BITC-induced cell death was completely prevented by pretreatment with thiol-containing redox compounds including N -acetyl-l -cysteine (NAC), glutathione (GSH), dithiothreitol, and 2-mercaptoethanol, but not free radical scavengers mito-TEMPO, catalase, apocynin, l -NAME and mannitol. BITC rapidly produced reactive oxygen species and nitric oxide, triggered oxidative DNA damage. BITC effectively decreased the intracellular GSH and GSH/GSSG ratio and redox balance recovery by thiol-containing redox compounds, but not by free radical scavengers. Accordingly, redox stresses-DNA damage response (DDR) activated ATM, Chk2, p53, and p21 and subsequently resulted in G2 /M phase arrest by inhibiting Cdc2 and cyclin B1. Notably, BITC-induced apoptosis was associated with reduced Mcl-1 and Bcl-2 expression, diminished mitochondrial membrane potential (ΔΨm), and increased PARP cleavage. These BITC-induced redox stress-mediated DDR and apoptosis could be blocked by NAC and GSH. Therefore, BITC can be a rational drug candidate for oral cancer and acted via a redox-dependent pathway. Graphical abstract: Highlights: BITC inhibits human oral cancer cells via redox stresses-DNA damage response. The thiol-containing redox compounds rescue BITC-induced cell death. BITC-induced apoptotic cell death and reduced the expression of Bcl-2 and Mcl-1. BITC suppress the growth of oral cancer cells with less toxicity to normal cells. BITC has the potential as a rational drug candidate for oral cancer.